Versatile Coating of Lithium Conductive Li2TiF6 on Over-lithiated Layered Oxide in Lithium-Ion Batteries - Choi, Wonchang; Benayard, Anass; Park, Jin-Hwan; Park, Junho; Doo, Seok-Gwang; Mun, Junyoung (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
We demonstrate an easy and versatile approach to modify a cathode-surface with a highly lithium-ion conductive layer by coating it with Li2TiF6. The thin and homogeneous Li2TiF6 coating is introduced onto an over-lithiated layered oxide (OLO, namely Li1.17Ni0.17Co0.1Mn0.56O2) surface via simple co-precipitation at ambient temperature by using Li2CO3 and H2TiF6 aqueous solutions. The lithium-conductive fluoride coating is expected to effectively suppress the undesired electrochemical and thermal interfacial reactions involving the OLO, which is critical in improving cycle performance and thermal stability. After Li2TiF6 surface modification, the coated OLO materials showed high rate capability as well as long cyclability and improved thermal stability. The crystalline structure and surface microstructure of the prepared OLOs were investigated by X-ray diffraction, transmission electron microscopy, and X-ray photoelectron spectroscopy. Ultimately, the performances of the assembled lithium ion batteries were thoroughly investigated by electrochemical methods and thermal analysis. Crown Copyright (C) 2013 Published by Elsevier Ltd. All rights reserved.
Keywords: RICH COMPOSITION LI1.2MN0.525NI0.175CO0.1O2; ELECTROCHEMICAL PROPERTIES; HIGH-CAPACITY; CATHODE; SURFACE; ELECTRODES; STABILITY; BEHAVIOR